The metabolic relevance of type of locomotion in anaerobic testing: bosco continuous jumping test versus wingate anaerobic test of the same duration - Kaufmann, S.; Hoos, O.; Beck, A.; Fueller, F.; Latzel, R.; Beneke, R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To evaluate the metabolic relevance of type of locomotion in anaerobic testing by analyzing and comparing the metabolic profile of the Bosco Continuous Jumping Test (CJ30) with the corresponding profile of the Wingate Anaerobic Test (WAnT).